Biosynthesis of Polyunsaturated Fatty Acids from the Linoleic Acid Family in Cultured Cells - Tacconi de Alaniz, María Josefa (1977)
HTC cells (designated HTC for hepatoma tissue culture) were derived from the ascites form of a rat-carried Morris hepatoma 7288 C (Thompson et al, 1966). Previous studies have revealed that cells of this kind are able to desaturate and elongate fatty acids. In this respect it was demonstrated that culture HTC cells preserved the ability to desaturate stearic to oleic acid (Δ9 desaturase), α-linolenic acid to octdeca-6, 9,12,15-tetraenoic acid (Δ6 desaturase), and eicosa-8,11,14-trienoic acid to arachidonic acid (Δ5 desaturase) (Alaniz et al, 1975). They are also able to convert α-linolenic acid to higher homologs with 5 and 6 double bonds by desaturation and elongation reactions. These results also proved the existence of Δ4 desaturase activity (Alaniz et al, 1975). However, it was shown that the cell cultured in Swim’s medium supplemented with serum possessed a very low capacity to convert labeled linoleic acid of the medium to arachidonic acid. Nevertheless, these tumor cells readily converted eicosa-8,11,14-trienoic acid to arachidonic acid (Alaniz et al, 1975; Gaspar et al, 1975). Therefore, the difficulty of these cells to synthesize arachidonic acid from linoleic acid may reside in a step previous to the Δ5 desaturation of eicosa-8, 11, 14-trienoic acid. This step could be a Δ6 desaturation of linoleic acid. The discrepancy between the biosynthesis of linoleic and α-linolenic acid series is difficult to explain considering that the same enzyme desaturates linoleic and ±-linolenic acids in Δ6 position (Brenner and Peluffo, 1966) (Brenner, 1971; Brenner, 1974) (Ninno et al, 1974). For this reason it was important to investigate the routes of arachidonic acid synthesis from labeled linoleic acid and the possible incorporation of labeled acids in cell lipids.